Efektivitas Pemasangan Kateter Dengan Menggunakan Jelly Yang Dimasukkan Uretra Dan Jelly Yang Dioleskan Di Kateter Terhadap Respon Nyeri Pasien - Riandono, Bambang; Handoyo,; Indriati D.S, Dina (Jurusan Keperawatan FIKES UNSOED, 2008)
Catheter insertion represents very emergency situation and it is need medical teams who have good skill during performing insertion of catheter. If medical teams (nurses and doctor) do not have enough good skill it would make some medical complications and have uncomfortable situation to these patients.Ã‚Â The aim of this study was to analyze the effectiveness of catheter insertion by inserting lubricant into urethra and lubricating catheter toward pain level of patient at emergency room of Banyumas Public Hospital.This study used quasi experimental method with Post Test Only Control Group Design. The numbers of sample was 30 respondents and divided into two groups with 15 respondents as treatment groups and 15 respondents as control groups. Sample was taken by purposive sampling method. Pain level was measured byÃ‚Â Ã‚Â visual analog scale pain assessmentThe result show that there is significant differences of pain level of patient who isÃ‚Â insertedÃ‚Â catheter by inserting lubricantÃ‚Â intoÃ‚Â urethra and lubricatingÃ‚Â catheter at ( t =6.32,Ã‚Â p= 0.00). High level of pain was experiencing for patient who is inserted catheter by lubricating catheter than inserting lubricant into urethra